Implementasi Permainan Playdough Dalam Mengembangkan Kognitif TK Ceria Banjarrejo - Lia Ricka Pratama (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Early childhood education is for children aged 0-6 years. Early childhood is a unique individual who has a pattern of growth and development in physical and cognitive aspects. By using playdough media, children can recognize and memorize colors, understand the instructions given by the teacher, understand the concept of time, etc. This research was carried out with the aim of knowing 1) the cognitive development of children aged 4-6 years at kindergarten at ceria banjarrejo. 2) Find out about efforts to develop the cognitive abilities of children aged 4-6 years through playdough games at Ceria Banjarrejo Kindergarten. This type of research uses a qualitative approach, while the type of researcher used is descriptive which seeks to describe and interpret existing data. Data collection techniques in this research are observation, interviews and documentation. Based on the research results, it can be concluded that the cognitive development of children at the Ceria Banjarrejo Kindergarten using playdough media has developed well and is in accordance with the child's developmental stages. There are several findings that have been implemented by the teacher, namely: 1) The teacher prepares tools & materials in the form of flour, vegetable oil, water and a bowl. 2) The teacher gives instructions and guides the children on how to make playdough. 3) Teachers adjust learning media according to themes and sub-themes. 4) Children's cognitive development is stimulated by the presence of playdough media, for example the theme of me with my favorite sub-theme (ice cream), children are asked to make my favorite food (ice cream) then decorate it as creatively as possible. 5) The teacher evaluates the process of the activities carried out by asking how they felt when taking part in today's lesson and informing the children about the learning for the next day. Based on the research results, it can be concluded that playdough games are an effective and fun method for children and can develop children's cognitive abilities. Supporting factors are part of supporting learning to be carried out optimally in learning, namely the teacher prepares the media and place that will be used when learning activities take place and does not forget the collaboration between educators and student parents.